Study on Plantago major L. dan Phaseolus vulgaris L. chlorophyll and carotenoid content using as bioincator for air pollution - ENDANG ANGGARWULAN; SOLICHATUN SOLICHATUN (Biodiversitas Journal of Biological Diversity, 2007)
The aims of this research were to study using chlorophyll and carotenoid as bioindicator air quality. This research used completely randomized design 2 x 4 factorial with 5 replicates. The first factor was distance from source of exhaust automobile emissions, consists of 4 levels: 0,50, 100, and 200 m. The second factor was plant spesies, consist 2 level: Plantago major and Phaseolus vulgaris. Data collected were analyzed using Multiple Regression Analysis followed by Duncan Multiple Range Test in 5% confidence level. The result indicated that increasing distance from source exhaust automobile emission, increased growth and chlorophyll content. Chlorophyll content in Phaseolus is more sensitive as bioindicator for air pollution.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: chlorophyll, bioindicator, Planatago major, Phaseolus vulgaris.